Mathematics
Joey460
2015-10-29 01:50:48
Solve for x: y=(2x)/(x-1)
ANSWERS
suzieL
2015-10-29 04:32:50

y = (2x) / (x-1) Multiply each term by x -1 and simplify. 2x = yx -y Reorder to have all common terms on one side. 2x -yx = -y Factor x out of 2x -yx. x (2 -y) = -y Divide each term by 2 -y and simplify. x = (-y) / (2-y) Reorder 2 and -y. Factor -1 out of -y. x = (-y) / ((-y)+2) Rewrite 2 as -1(-2). Factor -1 out of -(y)-1(-2). x = -(y) / -(y-2) Simplify the expression. x = y / (y-2)

ADD ANSWER